Theoretical Studies on Cyclopropanation Reaction of Aluminum Carbenoid (CH3)2AlCH2I with Allylic Alcohol - Li, Zhaohui; Shen, Jinglin; Hu, Huiqun; He, Lizhen (Asian Journal of Chemistry, 2014)
The aluminum carbenoid (CH3)2AlCH2I promoted cyclopropanation reactions with allylic alcohol have been investigated. Two reaction channels have been found i.e., the methylene transfer and carbometalation pathways. On the basis of the energetics of the reactions pathways, the methylene transfer pathway (reaction barrier of 9-10.3 kcal/mol) is favored over the carbometalation pathway (about 30 kcal/mol) in the whole reactions. Our computational results are in good agreement with the experimental results performed by Andre B. Charette.